Muscle memory: myonuclear accretion, maintenance, morphology, and miRNA levels with training and detraining in adult mice. Issue 6 (2nd September 2020) - Murach, Kevin A.; Mobley, C. Brooks; Zdunek, Christopher J.; Frick, Kaitlyn K.; Jones, Savannah R.; McCarthy, John J.; Peterson, Charlotte A.; Dungan, Cory M.
Abstract: Background: In the context of mass regulation, 'muscle memory' can be defined as long‐lasting cellular adaptations to hypertrophic exercise training that persist during detraining‐induced atrophy and may facilitate future adaptation. The cellular basis of muscle memory is not clearly defined but may be related to myonuclear number and/or epigenetic changes within muscle fibres. Methods: Utilizing progressive weighted wheel running (PoWeR), a novel murine exercise training model, we explored myonuclear dynamics and skeletal muscle miRNA levels with training and detraining utilizing immunohistochemistry, single fibre myonuclear analysis, and quantitative analysis of miRNAs. We also used a genetically inducible mouse model of fluorescent myonuclear labelling to study myonuclear adaptations early during exercise. Results: In the soleus, oxidative type 2a fibres were larger after 2 months of PoWeR ( P  = 0.02), but muscle fibre size and myonuclear number did not return to untrained levels after 6 months of detraining. Soleus type 1 fibres were not larger after PoWeR but had significantly more myonuclei, as well as central nuclei ( P  < 0.0001), the latter from satellite cell‐derived or resident myonuclei, appearing early during training and remaining with detraining. In the gastrocnemius muscle, oxidative type 2a fibres of the deep region were larger and contained more myonuclei after PoWeR ( P  < 0.003), both of which returned to untrained levels after detraining. In the gastrocnemius and plantaris, two muscles where myonuclear number was comparable with untrained levels after 6 months of detraining, myonuclei were significantly elongated with detraining ( P  < 0.0001). In the gastrocnemius, miR‐1 was lower with training and remained lower after detraining ( P  < 0.002). Conclusions: This study found that (i) myonuclei gained during hypertrophy are lost with detraining across muscles, even in oxidative fibres; (ii) complete reversal of muscle adaptations, including myonuclear number, to untrained levels occurs within 6 months in the plantaris and gastrocnemius; (iii) the murine soleus is resistant to detraining; (iv) myonuclear accretion occurs early with wheel running and can be uncoupled from muscle fibre hypertrophy; (v) resident (non‐satellite cell‐derived) myonuclei can adopt a central location; (vi) myonuclei change shape with training and detraining; and (vii) miR‐1 levels may reflect a memory of previous adaptation that facilitates future growth.